PENGARUH PENERAPAN METODE SOSIODRAMA TERHADAP HASIL BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN AQIDAH AKHLAK DI MTS NW PERIAN - Muhibbin - Muhibbin (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2020)
This study aims to determine how the influence of the application of the sociodrama method to the learning outcomes of class VIII students on the subject of aqidah morals in MTs NW Perian. The research approach used is a quantitative approach. The data collection techniques used, observation, tests, questionnaires and documentation. while the data analysis technique uses simple linear regression formula. The population in this study were all students of class VIII MTs NW Perian, amounting to 106 people then the sample used was 21. The results of the calculation using the regression formula then obtained the results that F count> F table (14.128> 4.38) by doing a significance test, then do a linearity test, where the results of the linearity test are found in numerator = 1 and in denominator = 18 with a significance level of 5%, then F arithmetic <F table (0.634 <4.41). So based on these calculations, Ho is rejected and Ha is accepted, in other words it can be concluded that there is an effect of the application of the Sociodrama method to the learning outcomes of Grade VIII students on the Code of Conduct in the MTs NW Perian.